A theoretical and experimental study of a novel refrigerant compressor - Eames, I. W. (Cranfield University, 1989)
The aim of this thesis is to evaluate the findings of research undertaken into the design manufacture and testing of a novel refrigeration compressor for use in packaged air conditioner units of the type used in railway passenger transport systems.